Simulating Net Ecosystem Productivity (NEP) in Mediterranean Pine Forests (Pinus brutia) During the 21st Century: The Effect of Leaf Area Index and Elevation - Christodoulos I. Sazeides; Nikolaos M. Fyllas (Plants)
The Gross Primary Productivity (GPP) of Mediterranean forest is expected to change over the 21st century due to the warmer and drier conditions. In this study, we present a process-based forest carbon-flux model, where stand structure and soil heterotrophic respiration have been parameterized with long-term monitoring data in a Mediterranean Pinus brutia. Ten. forest. The developed model was validated using an independent annual tree-ring increment dataset from the 1980–2020 period (baseline climate) across a post-fire gradient (four plots) and an elevation gradient (five plots). Additionally, the model was forced with two downscaled climate change scenarios (RCP4.5 and RCP8.5) for the 2020–2100 period. Average GPP, Net Primary Productivity (NPP), ecosystem Respiration (Reco) and Net Ecosystem Productivity (NEP) were calculated for two future time periods (2051–2060 and 2091–2100) under the two climate change scenarios and compared along the two gradients. Under baseline climate conditions, our simulations suggest a temperature sensitivity of GPP and Reco, as expressed along the elevation gradient. However, the effect of stand structure (represented through the site-specific leaf area index (LAI)) was more prominent, both along the elevation gradient and the post-fire chronosequence. Under the two climate change scenarios, a reduced GPP and an increased Reco lead to reduced NEP compared to baseline climate conditions across all study plots.